Survey on Prevalence of Vegadharana as a Risk Factor for Cardiac Disorders- An Observational Pilot Study (International Journal of Ayurveda and Pharma Research, 2021)
The present era, which is a reflection of changing major driving forces such as social, economic and cultural due to globalization, urbanization and population ageing. By this change, there is raise in the prevalence of certain non-communicable diseases. Cardiac disorders are among such which stands first in increasing mortality rate about 31% globally. Now a day, the prevalence rate is increasing due to behavioral risk factors like tobacco use, unhealthy diet, obesity, physical inactivity, alcohol and smoking. People are also at higher risk of these disorders with the presence of high risk of one or more already established disease conditions like Hyperlipidemia, Hypertension, Diabetes mellitus etc. Indians are being affected by high rates of these major risk factors which are striking for cardiac disorders at an earlier age almost 33% earlier than other demographical regions.Considering all these many organizations like MRFIT, American Heart association, National Lipid organization etc. are conducting various trials since four decades to establish the appropriate relation with risk factors to plan the better lines of management. Ayurveda explains about the concept of Dharaneeya and Adharaneeya vegas, where in Acharyas emphasize that many of the systemic diseases are caused by the forceful suppression of natural urges. Among 13 Dharaneeya vegas 9 are found to be the risk factors in causing various cardiac disorders. With this regard to explore and to assess the prevalence of Vegadharana as risk factor for cardiac disorders, an attempt has made as a pilot survey study on 40 cardiac patients. Aim: To understand the Prevalence and epidemiology of Vegadharana in Cardiac disorders. To observe the Co-relation between Vegadharana and Cardiac disorders. Methodology: It is a Pilot observational study done by using a survey strategy. The questionnaire method in an electronic format was used to collect the data. Descriptive statistics and Co-relation Co-efficient was used to analyze the data obtained. Result: In this Pilot study, the sum of the prevalence of Vegadharana was observed it was found that the frequency of Vegadharana was more in cardiac individuals, especially the category of few times and sometimes with n value=76 and 64 respectively. Conclusion: With the above data, it can be concluded that; Vegadharana has an impact on the expectancy of Cardiac disorders. The data also revealed the co-relation of Vegadharana in permutation which are signifying as higher risk factors in causing cardiac disorders.